Arginase inhibition suppresses lung metastasis in the 4T1 breast cancer model independently of the immunomodulatory and anti-metastatic effects of VEGFR-2 blockade. (3rd June 2017) - Secondini, Chiara; Coquoz, Oriana; Spagnuolo, Lorenzo; Spinetti, Thibaud; Peyvandi, Sanam; Ciarloni, Laura; Botta, Francesca; Bourquin, Carole; Rüegg, Curzio
ABSTRACT: Tumor angiogenesis promotes tumor growth and metastasis. Anti-angiogenic therapy in combination with chemotherapy is used for the treatment of metastatic cancers, including breast cancer but therapeutic benefits are limited. Mobilization and accumulation of myeloid-derived suppressor cells (MDSC) during tumor progression and therapy have been implicated in metastasis formation and resistance to anti-angiogenic treatments. Here, we used the 4T1 orthotopic syngenic mouse model of mammary adenocarcinoma to investigate the effect of VEGF/VEGFR-2 axis inhibition on lung metastasis, MDSC and regulatory T cells (Tregs). We show that treatment with the anti-VEGFR-2 blocking antibody DC101 inhibits primary tumor growth, angiogenesis and lung metastasis. DC101 treatment had no effect on MDSC mobilization, but partially attenuated the inhibitory effect of mMDSC on T cell proliferation and decreased the frequency of Tregs in primary tumors and lung metastases. Strikingly, DC101 treatment induced the expression of the immune-suppressive molecule arginase I in mMDSC. Treatment with the arginase inhibitor N ω -hydroxy-nor-Arginine (Nor-NOHA) reduced the inhibitory effect of MDSC on T cell proliferation and inhibited number and size of lung metastasis but had little or no additional effects in combination with DC101. In conclusion, DC101 treatment suppresses 4T1 tumor growth and metastasis, partially reverses the inhibitory effect of mMDSC on T cell proliferation, decreases Tregs in tumors and increases arginase I expression in mMDSC. Arginase inhibition suppresses lung metastasis independently of DC101 effects. These observations contribute to the further characterization of the immunomodulatory effect of anti-VEGF/VEGFR2 therapy and provide a rationale to pursue arginase inhibition as potential anti-metastatic therapy.